Population Pharmacokinetics of Rilotumumab, a Fully Human Monoclonal Antibody Against Hepatocyte Growth Factor, in Cancer Patients. Issue 1 (1st November 2013) - Zhu, Min; Doshi, Sameer; Gisleskog, Per O.; Oliner, Kelly S.; Perez Ruixo, Juan Jose; Loh, Elwyn; Zhang, Yilong
<x xml:space="preserve">Abstract</x> Rilotumumab is an investigational, fully human, monoclonal antibody immunoglobulin G2 against hepatocyte growth factor (HGF) that blocks the binding of HGF to its receptor MET and has shown trends toward improved survival in a phase 2 clinical trial in gastric cancer. To characterize rilotumumab pharmacokinetics in patients with cancer and to identify factors affecting the pharmacokinetics, rilotumumab concentration data from seven clinical trials were analyzed with a nonlinear mixed‐effect model. We found that rilotumumab exhibited linear and time‐invariant kinetics over a dose range of 0.5–20 mg/kg. Typical systemic clearance and central volume of distribution were 0.184 L/day and 3.56 L, respectively. Body weight is the most significant covariate, and sex, cancer type, coadministration of chemotherapeutics, baseline plasma HGF and tumor MET levels, and renal and hepatic functions did not have an effect on rilotumumab pharmacokinetics. The concentration–time profiles for the rilotumumab clinical regimens were projected well with the model. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:328–336, 2014